2008
DOI: 10.1108/09526860810890477
|View full text |Cite
|
Sign up to set email alerts
|

The role of expectations in patients' hospital assessments

Abstract: Baskent University multidisciplinary healthcare teams have performed periodic patient satisfaction surveys in order to identify strengths and problem areas, formulate the quality improvement objectives and monitor progress towards achieving these objectives. However, patient satisfaction survey results are often highly positive. In these cases, improving care is not easy because measures are not sensitive enough to changes. Therefore a more sensitive measurement tool based on the SERVQUAL scale was developed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 17 publications
4
42
1
1
Order By: Relevance
“…The result of the study showed that there was negative association between level of education with patients' satisfaction of inpatient care in RSUD Dr. Moewardi, however it is statistically insignificant. The result of the study is in accordance with Bakar et al, (2008) in Dengjuin et al, (2009) that patients with high level of education possess higher expectation and intention compared to those with low income. High expectation tends to make patient unsatisfied with healthcare service.…”
Section: Discussionsupporting
confidence: 81%
“…The result of the study showed that there was negative association between level of education with patients' satisfaction of inpatient care in RSUD Dr. Moewardi, however it is statistically insignificant. The result of the study is in accordance with Bakar et al, (2008) in Dengjuin et al, (2009) that patients with high level of education possess higher expectation and intention compared to those with low income. High expectation tends to make patient unsatisfied with healthcare service.…”
Section: Discussionsupporting
confidence: 81%
“…The patients without insurance had lower trust score. In the previous studies, it was confirmed that the evaluation of the patients with insurance coverage compared with the patients without such protection is more positive concerning the services they receive from the hospital (20). The patient's health status was also influential on the patient's trust to the hospital and the patients who had evaluated their health status as good at discharge time, had a high-trust score.…”
Section: Discussionmentioning
confidence: 74%
“…This finding is in line with several previous researches in Iran 24,25 and elsewhere. 26,27 (Results of previous research should be mentioned in the introduction.) In the other hand, there are also some studies in other countries such as Spain 28 and Malaysia, 29 which have shown a positive gap between the patients’ expectations and perceptions of the quality of healthcare services.…”
Section: Discussionmentioning
confidence: 99%